Effectiveness Human Resource Management of Schools in Special Areas Under Tak Primary Educational Service Area Office 1 - Nakthai, Natthapon; Dokchan, Phasakorn; Rojanatrakul, Tanastha (Journal of Graduate MCU KhonKaen Campus, 2025)
This independent study aimed to 1) study the effectiveness of personnel administration in schools in special areas under the Office, 2) compare opinions of teachers and educational personnel on the effectiveness of personnel administration in schools in special areas under the Office, classified by personal factors and 3) study problems, obstacles, and guidelines for personnel administration in schools in special areas under the Office. The research was conducted according to the quantitative research method using a survey research study from questionnaires with 108 school administrators and teachers, collected from the entire population. Data were analyzed using frequency, percentage, mean, standard deviation, and t-test, F-test. The research results found that 1) The overall level of effectiveness of personnel management in schools in special areas was at a high level. 2) The comparison of opinions found that teachers and personnel with different genders, ages, education levels, positions, incomes, period of employment, and academic statuses had no different opinions on the effectiveness of personnel management in schools in special areas. Therefore, the hypothesis was rejected. 3) Problems, obstacles, and approaches to personnel management in schools in special areas found that in terms of problems and obstacles in personnel management, the preparation of workforce plans was unable to respond to the workforce management plans and the personnel obtained were not consistent with the needs of the educational institutions, including the inconvenience of traveling to work in some areas and the difficulty of travel and in terms of personnel management guidelines, it was to fucus on the context of the area by studying and analyzing the needs of teachers and educational personnel in order to respond to the management of personnel and being consistent with the needs of educational institutions as well, including supervision, which should be different from other areas by being flexible and adjusting the dress code and working hours to be appropriate and consistent with the terrain to facilitate travel.